NLRP3 inflammasome-dependent pyroptosis is proposed to be involved in the mechanism of age-dependent isoflurane-induced cognitive impairment - Yin, Lei (J Neuroinflammation, 2018)
Wang Z et al. recently published a paper, titled “Critical role of NLRP3-caspase-1 pathway in age-dependent isoflurane-induced microglial inflammatory response and cognitive impairment”. The finding in this paper is consistent with our previous study on NLRP3-caspase-1 pathway. Here, we propose that NLRP3 inflammasome-dependent pyroptosis may be involved in the mechanism of age-dependent isoflurane-induced cognitive impairment and discuss that inhibiting NLRP3 inflammasome activation with a novel inhibitor MCC950 may ameliorate age-dependent isoflurane-induced neuro-inflammation.